Case of an Unusual Suprascapular Neuropathy: Case Report and Literature Review - Sevgi İkbali Afşar; Metin Karataş (Galenos Yayinevi, 2018)
Suprascapular neuropathy is a rare cause of shoulder pain and muscle weakness. Common causes include space-occupying lesions such as paralabral cysts, soft tissue or bone tumors, recurrent overhead activities in athletes, direct trauma, fractures of the scapula and iatrogenic causes. Diagnosis of suprascapular neuropathy can be difficult due to overlap in the clinical presentation with cervical region and other pathologies of the shoulder. We present a 33-year-old male patient admitted to our clinic with complaints of left shoulder pain and arm weakness starting in 8 months ago. The clinical and electrophysiological evaluations confirmed the left suprascapular nerve lesion at suprascapular notch level. This case is presented to emphasize that suprascapular neuropathy should keep in mind in the differential diagnosis of shoulder pain also without of a mass, trauma or excessive physical activity that may cause the neuropathy.